Efficient Visible Light Photocatalytic Oxidation of NO on F- and N-Codoped Spherical TiO2 Synthesized via Ultrasonic Spray Pyrolysis. (6th November 2012) - Huang, Jianhui; Cheuk, Wahkit; Wu, Yifan; Lee, Frank S. C.; Ho, Wingkei
Abstract : The fluorine- and nitrogen-codoped TiO2 was synthesized by ultrasonic spray pyrolysis method with titanium tetrafluoride and urea as precursor. The codoped TiO2 was characterized by X-ray diffractometry (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), diffuse reflectance spectroscopy (DRS), and X-ray photoelectron spectroscopy (XPS). Nitric oxide (NO) photocatalytic oxidation in gas-phase medium was employed as a probe reaction to evaluate the photocatalytic reactivity of the catalysts. The results indicated that spherical codoped TiO2 photocatalysts with unique puckered surface were obtained by this method. The codoped catalysts have solely anatase crystalline structure. The optical characterization of the codoped catalysts showed that the codoped samples could be excited by visible light photons in the 400–550 nm and could efficiently oxidize NO under visible light irradiation. The mechanism of special morphology formation of prepared codoped TiO2 structure is also discussed.